CD38-targeted attenuated interferon alpha immunocytokine activates both innate and adaptive immune cells to drive anti-tumor activity - James F. Sampson; Hong Zhang; Dongmei Zhang; Mingying Bi; Adam Hinthorne; Sakeena Syed; Yuhong Zhang; Nibedita Chattopadhyay; Sabrina Collins; Sarah Pogue; Pia Björck; Michael Curley (PLoS ONE, 2025)
Recombinant interferon alpha (IFNα) has been used to treat cancer patients for over 30 years; however, its clinical utility has been limited by a narrow therapeutic index. Given the recognized anti-tumor and immunomodulatory impacts of IFNα, the development of novel strategies to harness these attributes while minimizing associated toxicity could provide significant benefit for patients. The concept of attenuating IFNα binding affinity for its receptor was conceived to address this challenge and led to the development of CD38-targeted Attenukine™, a CD38-targeted antibody attenuated IFNα immunocytokine. In this study, we sought to delineate the effects of targeting AttenukineTM specifically to tumor cells and/or immune cells using an antibody to CD38, a cell surface glycoprotein expressed on certain tumor and immune cells, using different mouse models and anti-human or anti-mouse CD38-targeted Attenukine™. Our results demonstrate that an anti-human CD38 AttenukineTM inhibits tumor growth through direct anti-proliferative effects of IFNα on CD38 + tumor cells as well as by indirectly modulating the anti-tumor immune response. In various in vivo models leveraging syngeneic mice bearing tumors with or without CD38 expression, administration of CD38-murine AttenukineTM mediated anti-tumor efficacy with increased immune activation and intra-tumoral infiltration. These data point to a potential dual mechanism of action for CD38-targeted Attenukine™, involving both tumor- and immune-directed effects, and highlight the potential benefit of a CD38-targeted attenuated IFNα therapy to deliver the known effects of IFNαtreatment to a broad spectrum of patients, while limiting the toxicity typically associated with recombinant IFNα.